Influence of Surface Plasmon Resonance on Fluorescence Emission of Dye-doped Nanoparticles - Ha, Chu Viet; Brochon, J. C.; Nhung, Tran Hong (Communications in Physics, 2016)
The influence of the surface plasmon of gold nanoparticles on the optical properties of the fluorescent nanoparticles in aqueous solution have been investigated. The fluorescence of nanoparticles can be enhanced or quenched in the presence of gold nanoparticles depending on the domination of energy transfer mechanisms: radiating surface plasmon coupling emission or F"orster energy transfer from fluorescent particles to gold particles, which exciting absorbing plasmon. The fluorescence enhancement or quenching is attributed to the increase or decrease of radiative recombination rates, respectively. The parameters of the energy transfer between fluorescent nanoparticles (dye molecules encapsulated in silica nanoparticles) and nano golds have been estimated. The results show that the interactions between nanoparticles depend on the size of both fluorophores (as donors) and gold nanoparticles (as acceptors).